Prediction of all-cause mortality with malnutrition assessed by controlling nutritional status score in patients with heart failure: a systematic review and meta-analysis. Issue 7 (30th July 2022) - Li, Huiyang; Zhou, Peng; Zhao, Yikai; Ni, Huaichun; Luo, Xinping; Li, Jian
Abstract: Objective: The aim of this meta-analysis was to investigate the association between malnutrition assessed by the controlling nutritional status (CONUT) score and all-cause mortality in patients with heart failure. Design: Systematic review and meta-analysis. Settings: A comprehensively literature search of PubMed and Embase databases was performed until 30 November 2020. Studies reporting the utility of CONUT score in prediction of all-cause mortality among patients with heart failure were eligible. Patients with a CONUT score ≥2 are grouped as malnourished. Predictive values of the CONUT score were summarized by pooling the multivariable-adjusted risk ratios (RR) with 95 % CI for the malnourished v . normal nutritional status or per point CONUT score increase. Participants: Ten studies involving 5196 patients with heart failure. Results: Malnourished patients with heart failure conferred a higher risk of all-cause mortality (RR 1·92; 95 % CI 1·58, 2·34) compared with the normal nutritional status. Subgroup analysis showed the malnourished patients with heart failure had an increased risk of in-hospital mortality (RR 1·78; 95 % CI 1·29, 2·46) and follow-up mortality (RR 2·01; 95 % CI 1·58, 2·57). Moreover, per point increase in CONUT score significantly increased 16% risk of all-cause mortality during the follow-up. Conclusions: Malnutrition defined by the CONUT score is an independent predictor of all-cause mortality in patients with heart failure. Assessment of nutritional status using CONUT score would be helpful for improving risk stratification of heart failure.